Electrical properties of low-temperature SiO2 thin films prepared by plasma-enhanced atomic layer deposition with different plasma times - Taehyeon Kim (AIP Publishing LLC, 2021)
Silicon dioxide (SiO2) thin films were prepared by plasma-enhanced atomic layer deposition (PEALD) at a low temperature of 150 °C using di-isopropylaminosilane and oxygen with different plasma times. While SiO2 films deposited with a short plasma time of 0.5 s exhibited high leakage current, SiO2 films deposited with a plasma time of 7 s at 150 °C showed excellent dielectric properties, including a low current density of 4.8 × 10−9 A/cm2 at 1 MV/cm and a high breakdown field of 10.5 MV/cm, comparable to those of PEALD-SiO2 films deposited at 350 °C. As the plasma time increased from 0.5 to 7 s, the dielectric constant of SiO2 films decreased from 7.5 to 4.0, which was close to the value of stoichiometric SiO2. Appropriate conduction mechanisms of these SiO2 films with differing electrical characteristics by plasma time were examined. Analyses by x-ray photoelectron spectroscopy and secondary ion mass spectrometry revealed that the quality of SiO2 films largely depended on the amount of defects such as hydroxyl and hydrogen-related species generated by low-temperature deposition.